Pengaruh Latihan Otot Lengan Melalui Permainan Gerobak Dorong Terhadap Peningkatan Servis Atas Dalam Permainan Bola Voli di Ekstrakulikuler SDN Babakan - Dani Aji Suwandi; Entan Saptani; Dewi Susilawati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to determine the effect of arm muscle training through the wheelbarrow game on improving overhand serve skills in volleyball among extracurricular students at SDN Babakan. The research method used a quantitative approach with a quasi-experimental design employing a pretest-posttest control group design. The sample consisted of 26 students divided equally into an experimental group (13 students) and a control group (13 students). The experimental group received arm muscle training using the wheelbarrow game for 8 weeks (16 sessions), while the control group followed conventional training. The results showed that the experimental group achieved a greater improvement in overhand serve performance compared to the control group, with an average N-Gain score of 86.49 (high category), while the control group achieved 30.85 (low category). The Independent Samples t-Test showed a posttest significance value of 0.000 (p < 0.05), indicating a significant difference after treatment. In conclusion, arm muscle training through the wheelbarrow game has a significant and more effective impact on improving overhand serve skills in volleyball among SDN Babakan extracurricular students. Keywords: Volleyball, Extracurricular, Wheelbarrow Game, Arm Muscle Strength, Overhand Serve